Status of total and available boron in groundnut growing soils of Jaipur (Rajasthan) - Kumar, Pradeep; Rajput, S.G.; Yadav, B.L.; Maurya, P.K.; Yadav, Brijesh (Annals of Agricultural Research, 2014)
The relationship between total and available boron and their availability with soil properties were investigated in some groundnut growing area of five tehsil of Jaipur district of Rajasthan. The total boron content range from 25.80 to 38.50 mg kg-1 with the mean value 32.37 mg kg-1 soil, whereas the available boron content ranged from 0.25 to 0.55 mg kg-1 with mean of 0.36 mg kg-1 soil. The total boron positive and significant correlated with EC (0.417**) and positive correlated with CEC, O.C., silt and clay. On the other hand available boron positive correlated with CEC (0.597**), O.C. (0.956**), silt (0.794**) and clay (0.839**). Further deliberate the variation in total boron, pH2 and CaCO3 content of soil were the best predicators, as observed with pH2 (R2 = 0.887) followed by CaCO3 (R2 = 0.602) i.e. 88.7 and 60.2 per cent variation in total boron content, respectively.